Comparative and phylogenetic analysis of the complete chloroplast genomes of Uncaria (Rubiaceae) species - Dai, Jiangpeng; Liu, Qiaozhen; Xu, Xingyuan; Tan, Zhijie; Lin, Yuexia; Gao, Xiaoxia; Zhu, Shuang (Frontiers in Plant Science, 2023)
The genus Uncaria is famous for its high medicinal value. However, the high morphological similarities and unclear interspecific genetic relationships have posed challenges to the classification and identification of Uncaria species. Here, we newly sequenced six chloroplast genomes of Uncaria species, including U. hirsuta, U. rhynchophylla, U. rhynchophylloides, U. homomalla, U. sinensis and U. lancifolia.Comparisons among the chloroplast genomes of Uncaria species showed their conservation in structure, gene content and order. Ten highly variable loci could be potentially used as specific molecular markers in the identification of Uncaria species.The third position of codons tended to use A/U base, and natural selection contributed more to the formation of codon usage bias in comparison to mutation pressure. Four genes (rbcL, ndhF, rps8, ycf2) were detected to be subjected to positive selection. Phylogenetic analysis showed that the genus Uncaria was a monophyletic group, belonging to the tribe Naucleeae. What's more, U. sinensis was not a variant of U. rhynchophylla. U. rhynchophylloides and U. rhynchophylla were not the same species.The results of the comparative and phylogenetic analysis provide valuable references for further researches of classification, identification, breeding improvement and phylogenetic relationships in Uncaria species.